Pagetoid polyostotic fibrous dysplasia. (12th May 2015) - Hosalkar, Rashmi Maruti; Pathak, Jigna; Swain, Niharika; Mohanty, Neeta
Abstract : Fibrous dysplasia (FD) is a benign skeletal lesion occurring due to mutation of Gs α gene and involves one or multiple bones. We present a case of a 30-year-old female patient, with a 1-year history of swelling under her right eye that had gradually increased in size. Extraoral examination revealed a diffuse swelling extending anteroposteriorly from preauricular region to nasolabial fold, frontonasal region and superoinferiorly from zygoma to body of mandible, causing ipsilateral proptosis and contralateral deviation of nose. Intraoral examination showed obliteration of right upper and lower buccal vestibule. CT disclosed expansile lytic lesions involving multiple skull bones, jaws, sternum, rib and thoracic vertebrae. Histopathology displayed broad and interconnected trabeculae connected to the host bone exhibiting reversal lines resembling the mosaic pattern of Paget's disease. These features suggested pagetoid polyostotic FD. The patient underwent cosmetic recontouring and is under regular follow-up postoperatively.